VULNERABILITY IN CHILD DEVELOPMENT: THE INFLUENCE OF THE MOTHER'S YOUTH AND HEALTH CONDITIONS - Daniel Ignacio da Silva; Verônica de Azevedo Mazza (Universidade Federal do Paraná, 2014)
This exploratory qualitative research aimed to investigate nurses' understanding regarding vulnerability in child development. It was undertaken with 39 nurses working in Municipal Health Centers with the Family Health Strategy in Curitiba, Paraná, Brazil. A semi-structured interview was used for data collection, and dialectical hermeneutics for analysis, ethical principles being respected. The results indicated that nurses understand the mother's youth and health conditions as situations which are adverse to child development, and indicate the need for nurses to improve their care technologies which promote the health of teenage mothers, appropriately encourage breastfeeding and articulate an adequate network of social support for those mothers who are ill. The understanding of vulnerability in the care for the child allows the reorientation of the care model which, based in the principles of comprehensiveness and equity, may be directed at the needs of the child and her family.